Gram-scale, chemoselective synthesis of N-[2-(5-hydroxy-1H-indol-3-yl)ethyl]-2-oxopiperidine-3-carboxamide (HIOC). Issue 23 (3rd June 2015) - Setterholm, Noah A.; McDonald, Frank E.; Boatright, Jeffrey H.; Iuvone, P. Michael
Graphical abstract: Abstract: N -[2-(5-Hydroxy-1 H -indol-3-yl)ethyl]-2-oxopiperidine-3-carboxamide (HIOC) is a potent activator of the TrkB receptor in mammalian neurons and of interest because of its potential therapeutic uses. In the absence of a commercial supply of HIOC, we sought to produce several grams of material. However, a synthesis of HIOC has never been published. Herein we report the preparation of HIOC by the chemoselective N -acylation of serotonin, without using blocking groups in the key acylation step.